Odpowiedzi

2010-04-05T16:01:49+02:00
A=6* pierwiastek z 2 cm
b=10cm
Pp=a*a
Pp=(6*pierwiastek z 2) do kwadratu
Pp=72cm
Pb=2ah
h=pierwiastek z [10 do kwadratu - (3*pierwiastek z 2) do kwadratu]
h=pierwiastek z 82
Pb=2 * 6*pierwiastek z 2 * pierwiastek z 82
Pb=12* pierwiastek z 164
Pc=Pp+4*Pb
Pc=72+4 * 12*pierwiastek z 164
Pc=72+48*pierwiastek z 164
4 3 4
2010-04-05T16:03:24+02:00
A= 6 pierwiatek z 2
d= a pierwiastka z 2
d= 6 pierwiastka z 2 * pierwiastek z 2= 6*2=12
1/2d= 6
H kwadrat+ 6 kwadrat= 10 kwadrat
H kwadrat= 100-36
H= pierwiaastek z 64
H= 8
Pc= a kwadrat + 4 * 1/2a *h
pc= 6 pierwiastek z 2 + 4 * 1/2 * 6 pierwiastek z 2 * 8
Pc= 12 + 2* 6 pierwiastek z 2 * 8= 12+ 96 pierwiastek z 2